Effect of Audit Tenure, Audit Fee, Size of Public Accounting Firm, Auditor Specialization, and Audit Rotation on Audit Quality - Trianjani, Nia; Rahayu, Sri; Ridwan, Muhammad (PT. Riset Press International, 2023)
Audit quality is all possibilities (probability) where the auditor when auditing the client's financial statements can find violations that occur in the client's accounting system and report them in the audited financial statements, where in carrying out their duties the auditor is guided by auditing standards and the relevant public accountant code of ethics. This study aims to examine the effect of audit tenure, audit fees, size of public accounting firm, auditor specialization, and audit rotation on audit quality. Audit quality is measured using a dummy variable by looking at going concern opinions made by independent auditors, audit fees are measured by Ln (natural logarithm), audit tenure is measured by calculating the number of years in which the same auditor has engaged the client, size of public accounting firm, specialization auditors, and rotation is measured using a dummy variable. The population in this study are Transportation and Logistics Service companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period which have been audited. The sample selection was carried out using purposive sampling method. The analytical method used to test the hypothesis is logistic regression analysis. The results of this study indicate that audit specialization has an effect on audit quality, while audit tenure, audit fees, size of a public accounting firm, and audit rotation have no effect on audit quality.